Company Size as a Moderating Determinant of Going Concern Audit Opinion (GCAO) on Emphasis of Matter (EOM) Paragraph - Winarta, Wiwiek; Sailendra, Sailendra (Dinasti Publisher, 2024)
This study aims to examine the effect of solvency and asset turnover on the company's chances of receiving a GCAO on EOM paragraph, with company size as a moderating variable. The research focuses on companies in the hospitality industry listed on the Indonesia Stock Exchange during the Covid-19 pandemic in the 2020-2022 period. The independent variables analyzed include solvency and asset turnover, while the dependent variable is the GCAO on EOM paragraph. This research method uses a purposive sampling technique to select 28 companies as samples for the 2020-2022 period. Data analysis was carried out using logistic regression implemented through the EViews application. The results of the analysis show that the higher the debt or low solvency, the higher the chance of the company receiving a GCAO on EOM paragraph. Meanwhile, the higher the asset turnover, the lower the chance of the company receiving a GCAO on EOM paragraph. In addition, company size is proven to moderate the effect of solvency and asset turnover on the chances of receiving a GCAO on EOM paragraph. In conclusion, companies with high solvency and high asset turnover during the Covid-19 pandemic can maintain their business continuity, so auditors do not feel the need to issue a GCAO on EOM paragraph.